Two-Dimentional Figure Learning Through Problem Based Learning in Class V Students of Primary Schools - Rahmah Kumullah; Ahmad Yulianto (Department of Mathematics Education, Faculty of Teacher Training and Education, Wisnuwardhana University of Malang, 2020)
The problem of this research is the low student learning outcomes in mathematics subject class V Pai State Primary School. The purpose of this study was to improve mathematics learning outcomes through problem-based learning in fifth grade students. This type of research uses a Class Action Research that includes cycles of planning, implementation, observation, and reflection. The research subjects were teachers and fifth grade students with a total of 20 students, consisting of 9 men and 11 women. Data collection techniques used were observation, testing and documentation. Analysis of the data used is qualitative and quantitative. The results showed an increase in student learning activities and outcomes. This increase can be seen from each cycle. In the teaching activities of teachers and student learning activities have increased. In the first cycle, the teaching activities of teachers and students were in the moderately increased category in the second cycle being a good category. Improvements also occurred in student learning outcomes. In the first cycle, the classical completeness which has not been determined and is in the inadequate category has not yet been achieved. In cycle II student learning outcomes have improved, it is seen from the average value that has increased and is in the very good category. The conclusion of this study is that the existence of teacher teaching activities and student learning activities in learning mathematics by applying problem-based learning can improve student learning outcomes in mathematics subjects in Class V Pai State Primary School